2013
DOI: 10.1523/jneurosci.1886-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Adaptive Processing of Stimulus Intensity in Two Major Nuclei of the Somatosensory Brainstem

Abstract: Tactile information ascends from the brainstem to the somatosensory cortex via two major parallel pathways, lemniscal and paralemniscal. In both pathways, and throughout all processing stations, adaptation effects are evident. Although parallel processing of sensory information is not unique to this system, the distinct information carried by these adaptive pathways remains unclear. Using in vivo intracellular recordings at their divergence point (brainstem trigeminal complex) in rats, we found opposite adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Neuronal response adaptation has been observed at all stages of processing 12 , 14 19 . The degree of adaptation depends mainly on the frequency of whisker stimulation 12 , 17 19 , its intensity (in terms of its amplitude and velocity) 14 , 15 , and the cortical state 55 , 56 . Consistent with previous studies, we found that for most of the recorded neurons (~90%), the evoked response decreased from the first deflection to a steady-state response level 12 , 17 , 21 , 22 45 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal response adaptation has been observed at all stages of processing 12 , 14 19 . The degree of adaptation depends mainly on the frequency of whisker stimulation 12 , 17 19 , its intensity (in terms of its amplitude and velocity) 14 , 15 , and the cortical state 55 , 56 . Consistent with previous studies, we found that for most of the recorded neurons (~90%), the evoked response decreased from the first deflection to a steady-state response level 12 , 17 , 21 , 22 45 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellualr and intracellular recordings from the VPM and unit recordings from the PrV were performed as previously reported (Mohar et al, 2013 , 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Electrodes were inserted into the exposed brainstem at an angle of 2–7° in relation to the horizontal plane and in parallel to the sagittal plane, starting 2–3 mm lateral to the midline and 1 mm dorsal to the meeting point of the brainstem and cerebellum. PrV units were detected after advancing the electrode 3 mm from the insertion point (Mohar et al, 2013 , 2015 ). Extracellular signals were amplified using a model 3000 amplifier (A-M Systems, Sequim, WA, USA), bandpassed at 0.3–3 kHz and amplified between 1000–10,000 before digitized at 10 kHz using homemade acquisition software in LabView (National Instruments, Austin, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One possibility is that the weakening of surround normalization signals by adaptation enhances spatial integration [50]. Another is that pathways with ‘sensitizing’ adaptation effects — due, for instance, to weakened inhibition — allow the system to ‘hedge its bets’ [45,51,100]. Reducing neuronal responsivity may be a good strategy in the face of strong inputs, but it leaves the system vulnerable: if the environment suddenly changes, weak signals will be undetected.…”
Section: Introductionmentioning
confidence: 99%